Effect of Apixaban Pretreatment on Alteplase-Induced Thrombolysis: An In Vitro Study - Thalerová, Sandra; Pešková, Michaela; Kittová, Patrícia; Gulati, Sumeet; Víteček, Jan; Kubala, Lukáš; Mikulík, Robert (Frontiers in Pharmacology, 2021)
Benefit of thrombolytic therapy in patients with acute stroke, who are on anticoagulant treatment, not well addressed. The aim of this study was to investigate whether apixaban can modify the thrombolytic efficacy of alteplase in vitro. Static and flow models and two variants of red blood cell (RBC) dominant clots, with and without apixaban, were used. Clots were prepared from the blood of healthy human donors and subsequently exposed to alteplase treatment. Apixaban and alteplase were used in clinically relevant concentrations. Clot lysis in the static model was determined both by clot weight and spectrophotometric determination of RBC release. Clot lysis in the flow model was determined by measuring recanalization time, clot length and spectrophotometric determination of RBC release. In the static model, clots without apixaban; compared to those with apixaban had alteplase-induced mass loss 54±8% vs. 53±8%, p=1.00; RBC release 0.14±0.04 vs. 0.12±0.04, p=0.14, respectively. Very similar results were obtained if plasma was used instead of physiological buffered saline as the incubation medium. In the flow model, clot lysis without apixaban; compared to those with apixaban was as follows: recanalization time 107±46 min vs. 127±31 min, p=1.00; recanalization frequency 90±22% vs. 90±22%, p=1.00; clot volume reduction 32±15% vs. 34±10%, p=1.00; RBC release 0.029±0.007 vs. 0.022±0.007, p=0.16, respectively. Apixaban had no positive effect on alteplase-induced thrombolysis in both the in vitro static and flow models. Our data support current clinical practice, such that thrombolysis is contraindicated in stroke treatment for patients who have been treated with anticoagulants.